Strategic Exploration of Training and Development to Enhance Digital Marketing Competence in Human Resource Management - Kraugusteeliana, Kraugusteeliana; Suherlan; Az Zaakiyyah, Hizbul Khootimah (ADMAN: Journal of Contemporary Administration and Management, 2024)
In the context of globalization and the advancement of information technology, digital marketing has become a crucial element in business strategy. Digital transformation has brought significant changes in how companies interact with customers and the market. This research aims to discuss how training and development can serve as an effective strategy to enhance digital marketing competence within the realm of human resource management (HRM). The research methodology employed is a qualitative literature review, drawing data from Google Scholar within the timeframe of 2013-2023. A qualitative approach is utilized to delve into a profound understanding of the research topic through the analysis of scholarly literature and conceptual studies. The study's findings indicate that, in the pursuit of success in this digital era, a strategic exploration of training and development to enhance digital marketing competence in human resource management (HRM) is a crucial step. The rapid technological transformation has altered the business paradigm, and organizations striving for relevance must ensure that their HRM teams possess a profound understanding of digital marketing.